EoE CONNECT, the European Registry of Clinical, Environmental, and Genetic Determinants in Eosinophilic Esophagitis: rationale, design, and study protocol of a large-scale epidemiological study in Europe. (January 2022) - Lucendo, Alfredo J.; Santander, Cecilio; Savarino, Edoardo; Guagnozzi, Danila; Pérez-Martínez, Isabel; Perelló, Antonia; Guardiola-Arévalo, Antonio; Barrio, Jesús; Elena Betoré-Glaria, María; Gutiérrez-Junquera, Carolina; Ciriza de los Ríos, Constanza; Racca, Francesca; et al.
Background: The growing prevalence of eosinophilic esophagitis (EoE) represents a considerable burden to patients and health care systems. Optimizing cost-effective management and identifying mechanisms for disease onset and progression are required. However, the paucity of large patient cohorts and heterogeneity of practice hinder the defining of optimal management of EoE. Methods: EoE CONNECT is an ongoing, prospective registry study initiated in 2016 and currently managed by EUREOS, the European Consortium for Eosinophilic Diseases of the Gastrointestinal Tract. Patients are managed and treated by their responsible specialists independently. Data recorded using a web-based system include demographic and clinical variables; patient allergies; environmental, intrapartum, and early life exposures; and family background. Symptoms are structurally assessed at every visit; endoscopic features and histological findings are recorded for each examination. Prospective treatment data are registered sequentially, with new sequences created each time a different treatment (active principle, formulation, or dose) is administered to a patient. EoE CONNECT database is actively monitored to ensure the highest data accuracy and the highest scientific and ethical standards. Results: EoE CONNECT is currently being conducted at 39 centers in Europe and enrolls patients of all ages with EoE. In its aim to increase knowledge, to date EoE CONNECT has provided evidence on the effectiveness of first- and second-line therapies for EoE in clinical practice, the ability of proton pump inhibitors to induce disease remission, and factors associated with improved response. Drug effects to reverse fibrous remodeling and endoscopic features of fibrosis in EoE have also been assessed. Conclusion: This prospective registry study will provide important information on the epidemiological and clinical aspects of EoE and evidence as to the real-world and long-term effectiveness and safety of therapy. These data will potentially be a vital benchmark for planning future EoE health care services in Europe.